Characteristics, Covariances, and Average Returns: 1929 to 1997 - Davis, James L.; Fama, Eugene F.; French, Kenneth R. (Journal of Finance, 2000)
The value premium in U.S. stock returns is robust. The positive relation between average return and book‐to‐market equity is as strong for 1929 to 1963 as for the subsequent period studied in previous papers. A three‐factor risk model explains the value premium better than the hypothesis that the book‐to‐market characteristic is compensated irrespective of risk loadings.